Evaluasi Program Perkuliahan Berbasis Proyek pada Mata Kuliah Learning Planning On English Language Teaching - Sutrisno Sadji Evenddy; Ledy Nurlely (Peneliti.net, 2021)
The purpose of this study was to analyze the quality of implementation and assessment of project-based Learning planning on English Language Teaching courses at the Department of English Education, FKIP, Untirta. This study uses a goal-oriented evaluative approach (goal-oriented evaluation). Data collection techniques are done by observing, asking questions and documentation. Quantitative analysis was used in this data analysis. The conclusion of this study is that project-based learning planning is in accordance with the objectives of the lecture. (2) The quality of the implementation of the Learning planning on English language teaching course in the English education department, FKIP, Untirta is considered good. (3) The final grades for the Learning Planning on English Language Teaching lectures, FKIP, Untirta are already very good.